Generalized Composition Operators from ℬμ Spaces to QK,ω(p,q) Spaces - Haiying Li; Tianshui Ma (Abstract and Applied Analysis)
Let 0<p<∞, let -2<q<∞, and let φ be an analytic self-map of 𝔻 and g∈H(𝔻). The boundedness and compactness of generalized composition operators (Cφgf)(z)=∫0z‍f'(φ(ξ))g(ξ)dξ, z∈𝔻, f∈H(𝔻), from ℬμ (ℬμ,0) spaces to QK,ω(p,q) spaces are investigated.